Predictors of Ball Velocity in the Sitting Volleyball Serve: A Causal Analysis - Cavedon, Valentina; Sandri, Marco; Golia, Silvia; Brugnoli, Chiara; Bolčević, Filip; Zancanaro, Carlo; Milanese, Chiara (International Journal of Sports Medicine, 2023)
This study explored the performance of the Sitting Volleyball serve by investigating the causal factors associated with ball velocity. Thirty-seven athletes underwent anthropometry and strength assessment and performed ten successful maximal effort serves. Ball velocity was measured using a sports radar gun. The hip, shoulder, elbow and wrist angles at the instant of ball impact as well as the height of ball impact were estimated through two-dimensional motion analysis. The causal relationships between variables were described through a linear Structural Equation Model and a Directed Acyclic Graph. Results showed that a smaller hip angle determines a greater shoulder angle, which in turn causes a greater elbow angle. A more open elbow angle together with a greater vertical reach allowed for a greater height of ball impact. Finally, increased height of ball impact along with greater abdominal strength are beneficial for higher ball velocity. These results underlined that the Sitting Volleyball serve is a multifactorial stroke involving anthropometric, technical and strength factors and suggest that athletes should improve their abdominal strength and master the technique necessary to perform the serve with the shoulder and the elbow joints fully extended in order to produce the greatest possible impact on the ball.
Keywords: paralympic sport; kinematic analysis; physical impairment; structural equation model; direct acyclic graph